Integration of Landsat 8, gravity, and field data for exploration of gold mineralization in Gamba District, Northern Cameroon. (10th July 2021) - Ketchaya, Yanick Blaise; Dong, Guochen; Fotze, Quentin Marc Anaba; Carrino, Thais Andressa; Mandeng, Eugene Pascal Binam; Lemdjou, Yanick Brice; Assie, Konan Roger; Fodoue, Yaya; Wassouo Wadjou, Jacques
Abstract : Remote sensing is a robust and useful tool for providing high‐resolution image data and enabling reliable geological mapping during the initial stage of mineral exploration. One of its main applications is the extraction of lineaments and to locate alteration areas to target gold exploration. It has been long used in the Pan‐African belt of Cameroon to identify a hydrothermal alteration and a great number of lineaments associated with mineralizations. The study area located in the Pan‐African belt hosts numerous alluvial gold deposits where the primary mineralization was still largely poorly unknown until now, due to deep weathering. Therefore, remote sensing combined with field data is useful for targeting potential zones of primary gold resources involved in the hydrothermal and lineament systems. In this study, remote sensing data from Landsat 8 imagery were selected to map the distribution of hydrothermal minerals, and gravity data were interpreted for highlighting structural patterns related to the control of high‐potential zone for gold mineralization, generating a mineral prospect map. The lineaments network shows directions ranging from ENE‐WSW to E‐W, with main direction N45° and a secondary striking N275°. Image enhancement/processing techniques included the application of band ratio and principal component analysis that were helpful to demarcate potential alteration zones marked by iron oxide/hydroxides in which haematite and pyrite are used as proximal alterations and hydroxyl‐bearing minerals in which sericite (muscovite) is used as a marker of proximal alteration, while chlorite, epidote, biotite, quartz, and calcite are used as distal alteration zone, as described by field and petrographic data. The identified alteration zones display a high consistency with the known locations of gold occurrences (mining sites) and closely concordant with large‐scale gold mineralization in the study area. This study presents an integrated approach of Landsat 8 imagery with gravity data and field data for discovering primary mineral resources in a deep weathering area. Abstract : Regional lineaments from satellite images showing the spatial distribution, and high‐potential areas of gold mineralization in Gamba district.